Psychological Capital dan Career Commitment pada Karyawan Milenial Kantor Pusat Bank BRI - Anjani Faustina; Retno Kusumastuti (Universitas Diponegoro, 2022)
The millennial generation has the most significant number in the Indonesian labor market, the first technophile generation, and is highly productive. However, the millennial generation tends to focus on themselves and lacks commitment. Closely related to individual career development, career commitment is one of the main challenges in managing Human Resources (HR), especially in Bank BRI, which focuses on the millennial generation. Considering there is still no related research, especially in the banking sector in Indonesia, this study aims to analyze the effect of psychological capital on the career commitment of millennial employees through subjective well-being as mediation at the Bank BRI Headquarters. This study uses a quantitative approach with an explanatory type by distributing questionnaires to 150 millennial employees at the Bank BRI Headquarters. The results showed an influence of psychological capital on the career commitment of millennial employees through subjective well-being as mediation at the Bank BRI Headquarters. This study shows that millennial employees at Bank BRI tend to respond positively to matters related to their work and subjectively feel their well-being. Therefore, all of the company's support helped to increase the millennials employees' psychological capital and subjective well-being, which led to their high career commitment. Generasi milenial merupakan generasi yang mendominasi pasar kerja di Indonesia saat ini dan generasi pertama yang cakap berteknologi serta sangat produktif. Namun, generasi milenial cenderung berfokus pada dirinya sendiri dan kurang memiliki komitmen. Terkait erat dengan pengembangan karir individu, career commitment menjadi salah satu tantangan utama pengelolaan Sumber Daya Manusia (SDM), khususnya pada Bank BRI yang sedang berfokus pada generasi milenial. Mempertimbangkan belum adanya riset terkait, khususnya pada sektor perbankan di Indonesia, penelitian ini ditujukan untuk menganalisis pengaruh psychological capital terhadap career commitment karyawan milenial melalui subjective well-being sebagai mediasi di Kantor Pusat Bank BRI. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis eksplanatif dengan menyebarkan kuesioner kepada 150 karyawan milenial di Kantor Pusat Bank BRI. Hasil penelitian menunjukkan bahwa terdapat pengaruh psychological capital terhadap career commitment karyawan milenial melalui subjective well-being sebagai mediasi di kantor pusat Bank BRI. Penelitian ini menunjukkan bahwa karyawan milenial di Bank BRI cenderung merespons secara positif hal-hal terkait pekerjaannya dan secara subjektif merasakan kesejahteraan. Oleh karena itu, dukungan peningkatan psychological capital dan subjective well-being perusahaan mendorong terciptanya career commitment pada karyawan milenial.